Pig Farm Environment as a Potential Reservoir of ESBL-producing E. coli: A Systematic Review - Burahim, Fatima Zaira J.; Sapiandante, Desiree Jane A.; Ramos, Karlyn Louise B.; Garbino, Jeff Archie Mari P.; Lacambra, Fredric Nuel B.; Edem, Kurt Irwin I.; Espiritu, Mark Fiolo V.; Rillera, Danie Kaye C.; Tolenada, Charlene Princess S. (Asian Journal of Biological and Life Sciences)
Extended-spectrum beta-lactamases (ESBLs) are enzymes that can be observed in some bacterial strains, most commonly in Escherichia coli, which are resistant to various antibiotics, specifically beta-lactams. Having the ability to destroy active ingredients of certain antibiotics, the impacts of undesirable utilization of antibiotics increase the development of antibiotic-resistant bacteria, posing additional threats to public health. The purpose of this review is to evaluate the pig farm environments as potential reservoirs of ESBL-producing E. coli by its presence in water and soil samples, its gene prevalence, and its negative effects on public health through gathering credible studies from various databases and examining journals that have met the set review standards. Among the isolates from the six included studies, the existence of ESBL-producing E. coli was higher in water samples with 13.63% of isolates. From the four studies discussing the prevalence of ESBL-producing E. coli genes, the most dominant gene detected in water samples was blaCTX-M (40%), followed by blaTEM (9%), and blaSHV (0%). In soil samples, the blaCTX-M gene (36%) still predominates, then the blaSHV gene (27%), and lastly, the blaTEM gene (5%). Without concern for the sample type, the most dominant gene was the blaCTX-M gene (39%), followed by both blaTEM (8%) and blaSHV genes (8%). The data shows that unsanitary pig farms are potential sources for ESBLproducing E. coli. With its ability to resist antibiotics, the increasing distribution of this bacteria to different environmental matrices increases its risk of infections, thereby also affecting the health of the public.
Keywords: blaCTX-M; blaSHV; blaTEM; ESBL-E. coli; Pig Farms